2016
DOI: 10.1016/j.nicl.2016.11.001
|View full text |Cite
|
Sign up to set email alerts
|

The association between intra- and juxta-cortical pathology and cognitive impairment in multiple sclerosis by quantitative T 2 * mapping at 7 T MRI

Abstract: Using quantitative T2* at 7 Tesla (T) magnetic resonance imaging, we investigated whether impairment in selective cognitive functions in multiple sclerosis (MS) can be explained by pathology in specific areas and/or layers of the cortex.Thirty-one MS patients underwent neuropsychological evaluation, acquisition of 7 T multi-echo T2* gradient-echo sequences, and 3 T anatomical images for cortical surfaces reconstruction. Seventeen age-matched healthy subjects served as controls.Cortical T2* maps were sampled at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 40 publications
2
23
0
Order By: Relevance
“…The near universally stronger cGM and NAWM perfusion association and deteriorating perfusion metrics with disease progression also confirmed in prior studies 12,14,16, 26, 27 suggests that perfusion is sensitive to a common pathophysiological mechanism reflecting concomitant but not necessarily co-dependent cGM and WM pathology in MS. Findings are supported by a recently reported DTI study 8 suggesting that perfusion could serve as a useful surrogate of disease activity in addition to routine structural imaging.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…The near universally stronger cGM and NAWM perfusion association and deteriorating perfusion metrics with disease progression also confirmed in prior studies 12,14,16, 26, 27 suggests that perfusion is sensitive to a common pathophysiological mechanism reflecting concomitant but not necessarily co-dependent cGM and WM pathology in MS. Findings are supported by a recently reported DTI study 8 suggesting that perfusion could serve as a useful surrogate of disease activity in addition to routine structural imaging.…”
Section: Discussionsupporting
confidence: 72%
“…This assertion is supported by various pathological and imaging studies 8, 2224 which have shown that cGM lesions may develop prior to the appearance of WM plaques 22 , arise independently of, and are poorly correlated with T2h-l formation 23,24 . A number of pathological and imaging papers have increasingly implicated an independent etiology for cGM lesion formation attributed either to the direct presence of meningeal-derived neurotoxic substances or secondary microglial activation mediated through meningeal/supbial inflammation and manifest as a gradient of demyelination centered upon the subpial cortex 24, 27 .…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Recent pathologic studies indicate that there is involvement of gray matter structures as well. Gray matter atrophy and lesions can occur early in the disease and may correlate with degeneration, not just demyelination [10]. A consensus panel determined that brain volume is a valuable measure and should be included in the determination of whether or not there is evidence of disease activity at follow up visits [11].…”
Section: Discussionmentioning
confidence: 99%